Make. - Senese, Mike, 1975- (MAKE COMMUNITY, LLC, 2022)
No, you're not crazy: For years, it's been getting harder and harder to repair your stuff. From implementing proprietary components and specialized fasteners to withholding schematics and mandating repairs go through "authorized" outlets, modern companies do their best to make it difficult to fix the products you already own. This, by design, gives you no choice but to buy new things whenever your old things break. But it's still your stuff, and you should have the right to fix it. In this issue we hear from Right-to-Repair luminary Cory Doctorow and iFixit CEO Kyle Wiens about the uphill battle for policy progress at the national level in the U.S. and beyond. Plus, we look at how makers are already addressing repair needs in their own communities, from online meetups for repair advice to cultivating a repair mindset in students at a young age. Plus, more than 35 projects including: Build a GPS-guided parachute that guides your aerial payload back to you Construct a workspace fume hood that funnels toxic gasses out of harm's way Make an e-paper box that displays popular quotations via Reddit's hivemind 3D print a versatile vise that conforms snuggly to whatever it holds And much more!.